Legal challenges to the far-right: lessons from England and Wales - Alkiviadou, Natalie (Routledge studies in fascism and the far right, 2020)
Introduction -- Human rights and fundamental freedoms -- International framework -- European framework -- The far-right movement and criminal law -- Legal treatment of political parties -- Conclusion